The Routledge companion to Britain in the nineteenth century, 1815-1914 - Cook, Chris, 1945- (Routledge companions to history., 2005)
The Routledge Companion to Britain in the Nineteenth Century, 1815-1914 is an accessible and indispensable compendium of essential information on the Victorian and Edwardian eras. Using chronologies, maps, glossaries, an extensive bibliography, a wealth of statistical information and nearly two hundred biographies of key figures, this clear and concise book provides a comprehensive guide to modern British history from the end of the Napoleonic Wars to the outbreak of the First World War. As well as the key areas of political, economic and social development of the era,